Anti-necroptotic effects of human Wharton's jelly-derived mesenchymal stem cells in skeletal muscle cell death model via secretion of GRO-α. - Sang Eon Park; Soo Jin Kwon; Sun Jeong Kim; Jang Bin Jeong; Min-Jeong Kim; Suk-Joo Choi; Soo-Young Oh; Gyu Ha Ryu; Hong Bae Jeon; Jong Wook Chang (PLoS ONE)
Human mesenchymal stem cells (hMSCs) have therapeutic applications and potential for use in regenerative medicine. However, the use of hMSCs in research and clinical medicine is limited by a lack of information pertaining to their donor-specific functional attributes. In this study, we compared the characteristics of same-donor derived placenta (PL) and Wharton's jelly (WJ)-derived hMSCs, we also compared their mechanism of action in a skeletal muscle disease in vitro model. The same-donor-derived hWJ- and hPL-MSCs exhibited typical hMSC characteristics. However, GRO-α was differentially expressed in hWJ- and hPL-MSCs. hWJ-MSCs, which secreted a high amount of GRO-α, displayed a higher ability to inhibit necroptosis in skeletal muscle cells than hPL-MSCs. This demonstrates the anti-necroptotic therapeutic effect of GRO-α in the skeletal muscle cell death model. Furthermore, GRO-α also exhibited the anti-necroptotic effect in a Duchenne muscular dystrophy (DMD) mouse model. Considering their potential to inhibit necroptosis in skeletal muscle cells, hWJ-MSCs and the derived GRO-α are novel treatment options for skeletal muscle diseases such as DMD.